Personalising laboratory medicine in the 'real world': Assessing clinical utility, by clinical indication, of serum total B12 and Active-B12® (holotranscobalamin) in the diagnosis of vitamin B12 deficiency. (September 2021) - Murphy, Michael J; Brandie, Fiona; Ebare, Mildred; Harrison, Michelle; Dow, Ellie; Bartlett, William A; Craig, David
Background: Assessing the pre- and post-test probability of disease in the context of routine health care is challenging. We wished to study how test performance parameters relating to clinical utility vary by clinical indication in a 'real-world' setting. Methods: The diagnostic accuracy of serum total B12 and Active-B12 ® (holotranscobalamin) was evaluated in a primary care population, using serum methylmalonic acid as the reference standard. We used electronic requesting to establish the clinical indication for each request. Routine requests from primary care for serum total B12 were included if creatinine was also measured and estimated glomerular filtration rate was at least 60 mL/min/1.73 m 2 . Results: Clinical indications included peripheral neuropathy ( n  = 168), anaemia ( n  = 168), cognitive decline ( n  = 125), suspected dietary deficiency ( n  = 76), other ( n  = 362). For peripheral neuropathy, the area under the receiver operator curve ± 95% confidence interval (AUC ± CI) was 0.63 (0.54–0.71) ( P  = 0.002) for total B12 and 0.68 (0.60–0.77) ( P  < 0.0001) for Active-B12 ®. For anaemia, AUC ± CI was 0.56 (0.47–0.66) ( P  = 0.10) for total B12 and 0.69 (0.59–0.78) ( P  < 0.0001) for Active-B12 ®. For cognitive decline, AUC ± CI was 0.54 (0.43–0.65) ( P  = 0.26) for total B12 and 0.69 (0.58–0.80) ( P  = 0.0002) for Active-B12 ®. The pre–post-test change in probability of disease varied by clinical indication. Conclusion: Combining diagnostic accuracy studies and electronic testing in a 'real-world' setting allows clinical utility to be assessed by clinical indication. Wider application of this would permit more personalised laboratory medicine. In this study, diagnostic performance of total B12 and Active-B12 ® varied across all indications. Active-B12 ® provided better discrimination, but this may have reflected the cut-offs used.